2023
DOI: 10.1007/s42761-022-00167-w
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Modify Psychological Well-Being: Progress, Promises, and an Agenda for Future Research

Abstract: Psychological well-being, characterized by feelings, cognitions, and strategies that are associated with positive functioning (including hedonic and eudaimonic well-being), has been linked with better physical health and greater longevity. Importantly, psychological well-being can be strengthened with interventions, providing a strategy for improving population health. But are the effects of well-being interventions meaningful, durable, and scalable enough to improve health at a population-level? To assess thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The 4-H program and development of frameworks such as the pedagogy of care using processes such as exploration, engagement, reflection, articulation, and actualization may support development of purpose among youth ( 82 , 83 ). Interventions to clarify values and develop purpose in life are now freely available ( 77 ) and, more broadly, interventions for psychological well-being are available at scale with refinements being considered to provide meaningful effects ( 84 ). The recent call to consider prosociality, or positive other-regarding behaviors and beliefs, as a public health priority ( 85 ) would benefit from interventions that facilitate clarification of values and foster development of purpose at the individual and societal level ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 4-H program and development of frameworks such as the pedagogy of care using processes such as exploration, engagement, reflection, articulation, and actualization may support development of purpose among youth ( 82 , 83 ). Interventions to clarify values and develop purpose in life are now freely available ( 77 ) and, more broadly, interventions for psychological well-being are available at scale with refinements being considered to provide meaningful effects ( 84 ). The recent call to consider prosociality, or positive other-regarding behaviors and beliefs, as a public health priority ( 85 ) would benefit from interventions that facilitate clarification of values and foster development of purpose at the individual and societal level ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, an intervention on psychosocial well-being could be more favorable, particularly when considering its indirect effect via emotion-driven impulsiveness and its more feasible interventions at the population level [ 47 , 48 ]. Yet, actual interventions also yielded rather small effects on average due to heterogeneous settings such as different target populations or intervention intensities [ 49 ]. For instance, one intervention study on psychosocial well-being, also using the KINDL, found a small to moderate effect after a competence skill enhancement approach focusing on developing children’s positive emotions and strengths and a positive school climate [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This proposition aligns with a substantial body of literature emphasizing the influential role of academic self-concept in shaping individuals’ perceptions of their abilities and competencies ( Shavelson et al, 1976 ; Marsh and Martin, 2011 ). According to this theoretical framework, academic self-concept not only influences cognitive judgments but also plays a pivotal role in shaping emotional experiences within educational contexts ( Salami, 2011 ; Kubzansky et al, 2023 ). Positive academic self-concept is associated with increased satisfaction, reduced negative emotions, and an overall sense of personal fulfillment ( Wu et al, 2021 ; Hatun and Kurtça, 2022 ).…”
Section: Review Of the Literaturementioning
confidence: 99%